2020
DOI: 10.3390/pharmaceutics12060528
|View full text |Cite
|
Sign up to set email alerts
|

Key-Protease Inhibition Regimens Promote Tumor Targeting of Neurotensin Radioligands

Abstract: Neurotensin subtype 1 receptors (NTS1R) represent attractive molecular targets for directing radiolabeled neurotensin (NT) analogs to tumor lesions for diagnostic and therapeutic purposes. This approach has been largely undermined by the rapid in vivo degradation of linear NT-based radioligands. Herein, we aim to increase the tumor targeting of three 99mTc-labeled NT analogs by the in-situ inhibition of two key proteases involved in their catabolism. DT1 ([N4-Gly7]NT(7-13)), DT5 ([N4-βAla7,Dab9]NT(7-13)), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(35 citation statements)
references
References 50 publications
6
28
1
Order By: Relevance
“…The [ 99m Tc]Tc-DT5 was not included in this study, in view of its inferior uptake by AsPC-1 cells compared with [ 99m Tc]Tc-DT1 (Figure 2b). In addition, it displayed high renal values in mice during a previous study, most probably as a result of the pendant δ-amine of Dab 9 in the peptide chain [39]. We observe that the radioactivity in the blood and the body of mice has substantially cleared at 4 h pi.…”
Section: Biodistribution Of [ 99mmentioning
confidence: 47%
See 3 more Smart Citations
“…The [ 99m Tc]Tc-DT5 was not included in this study, in view of its inferior uptake by AsPC-1 cells compared with [ 99m Tc]Tc-DT1 (Figure 2b). In addition, it displayed high renal values in mice during a previous study, most probably as a result of the pendant δ-amine of Dab 9 in the peptide chain [39]. We observe that the radioactivity in the blood and the body of mice has substantially cleared at 4 h pi.…”
Section: Biodistribution Of [ 99mmentioning
confidence: 47%
“…Aiming to elucidate these findings, we further studied the cell binding capabilities and in vivo stability of the radiotracer. We observed that the Tle 12 /Ile 12 substitution led to poor binding/internalization of [ 99m Tc]Tc-DT6 in WiDr cells compared with non-Ile 12 -substituted radioligands (e.g., 1.0 ± 0.4% specific cell binding vs. 10.1 ± 2.3% of [ 99m Tc]Tc-DT1 at 1 h incubation; p < 0.0001) [39]. Furthermore, the in vivo stability of [ 99m Tc]Tc-DT6 was found to be surprisingly lower than expected from in vitro assays (only 55.1 ± 3.9% of the radiotracer detected intact in peripheral mice blood at 5 min pi).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Within the context of bradykinin and substance P, and their pro‐inflammatory actions, it is important to recognize that that another bioactive peptide neurotensin is also degraded by ACE and neprilysin (Kanellopoulos et al, 2020; Skidgel & Erdos, 2004). However, the clinical significance of elevated neurotensin levels in response to inhibition of ACE or neprilysin has not been systematically studied.…”
Section: Ace and Neprilysin In Degradation Of Bradykinin Substance Pmentioning
confidence: 99%